Outcome Analysis of Transition From Peritoneal Dialysis to Hemodialysis: A Population-Based Study - Tsai, Ming-Hsien; Chen, Yun-Yi; Jang, Tsrang-Neng; Wang, Jing-Tong; Fang, Yu-Wei (Frontiers in Medicine, 2022)
If a technical failure occurs during peritoneal dialysis (PD), the patients undergoing PD may be transitioned to hemodialysis (HD). However, the clinical outcomes of patients who have undergone such a transition are under studied. This study assessed whether patients undergoing HD who have transitioned from PD have the same clinical outcomes as HD-only patients. This research was a retrospective cohort study by searching a National Health Insurance research database for data on patients in Taiwan who had undergone HD between January 2006 and December 2013. The patients were divided into two groups, namely a case group in which the patients were transitioned from PD to HD and a HD-only control group, through propensity score matching at a ratio of 1:4 (n = 1,100 vs. 4,400 respectively).We used the Cox regression model to estimate the hazard ratios (HRs) for all-cause death, all-cause hospitalization, infection-related admission, and major adverse cardiac events (MACE). Those selected patients will be followed until death or the end of the study period (December 2017), whichever occurs first. Over a mean follow-up of 3.2 years, 1,695 patients (30.8%) died, 3,825 (69.5%) required hospitalization, and 1,142 (20.8%) experienced MACE. Patients transitioning from PD had a higher risk of all-cause death (HR: 1.36; 95% CI: 1.21–1.53) than HD-only patients. However, no significant difference was noted in terms of MACE (HR: 0.91; 95% CI: 0.73–1.12), all-cause hospitalization (HR: 1.07; 95% CI: 0.96–1.18), or infection-related admission (HR: 0.97, 95% CI: 0.80–1.18) between groups. Moreover, the risk of mortality in the case group was more significant within 2 years of the transition. Patients undergoing HD who transitioned from PD had a 36% higher risk of death than the HD-only patients, especially in the first two years after transition. Therefore, more caution and monitoring may be required for patients undergoing HD who transitioned from PD.